Anti-hemorrhagic Activity of Four Brazilian Vegetable Species Against Bothrops jararaca Venom - Nishijima, Catarine Massucato [UNESP]; Rodrigues, Clenilson Martins [UNESP]; Silva, Marcelo Aparecido [UNESP]; Lopes-Ferreira, Monica; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Molecular Diversity Preservation International-mdpi, 2009)
Around 20,000 snakebites are reported annually in Brazil and 90% of them are inflicted by species of the genus Bothrops. Intravenous administration of antibothropic antivenom neutralizes the systemic actions, but it is of little effect on the reversal of local symptoms and often induces adverse reactions, a context that drives the search for complementary treatments for snakebite accidents. Vegetable extracts with a range of antiophidian activities constitute an excellent alternative. In this study, we investigated the anti-hemorrhagic effects of Mouriri pusa Gardn. (Melastomataceae), Byrsonima crassa Niedenzu (Malpighiaceae), Davilla elliptica St. Hill. (Dilleniaceae) and Strychnos pseudoquina St. Hil. (Loganiaceae) against Bothrops jararaca venom. The methanolic extracts from M. pusa (leaves), B. crassa (leaves) and D. elliptica (leaves) showed total neutralization capacity against local hemorrhages. The amenthoflavone and quercetin fractions from B. crassa and the flavonoids fractions (quercetin and myricetin) from M. pusa and D. elliptica also showed total neutralization capacity. We conclude that flavonoids derived from myricetin, quercetin and amenthoflavone play an important role in the anti-hemorrhagic potential of these Brazilian vegetables species against B. jararaca venom.
Keywords: Flavonoids; Antiophidic plants; Anti-hemorrhagic; Bothrops jararaca